PERBEDAAN PENCAPAIAN KOMPETENSI SISWA DENGAN MENERAPKAN LKPD IPA BERORIENTASI MODEL PEMBELAJARAN PENINGKATAN KEMAMPUAN BERPIKIR KELAS VII SMPN 12 PADANG - Paramita Paramita; Murtiani Murtiani; Nurhayati Nurhayati (PILLAR OF PHYSICS EDUCATION, 2017)
This study aims to determine student competency achievement differences by applying an science student work sheet oriented learning model increased ability to think of the seventh grade students of SMPN 12 Padang. Type of research is Quasi-Experimental Research, with the study design Posttest-Only Control Group Design. The study population was all students of class VII SMPN 12 Padang enrolled in the academic year 2016/2017. Sampling techniques was purposive sampling techniques and continued by random sampling technique. The research data was taken from the attainment of students in the second grade sample. Based on the hypothesis test for a third achievement of competence using the t test at the 0,05 significance level obtained by each competence (attitudes, knowledge, and skills) in sequence are 6.49, 3.01, and 4.57. While the  . These results show that  , then   rejected or   accepted. This means that there are differences in student achievement by implementing science student work sheet oriented learning model increased ability to think of class VII SMPN 12 Padang